No Sedation, No Traction, and No Need for Assistance: Analysis of New Prakash’s Method of Shoulder Reduction - Tolgahan Kuru; Haci Ali Olcar; Ali Bilge; Gurdal Nusran; Recai Ozkilic; Canan Akman; Lakshmanan Prakash (Emergency Medicine International)
Background and Objective. Shoulder dislocations, which often occur anterior, account for about half of all dislocations. There are numerous reduction methods reported for the conservative treatment of acute anterior dislocations. However, there is still an ongoing search for an optimal method given the procedure time, possible complications, success rates, and need for sedation/analgesia in existing methods. This study seeks to explore the effectiveness and safety of Prakash’s method in the treatment of acute shoulder dislocations, which is a novel method in the treatment of anterior shoulder dislocations. Materials and Methods. A total of 19 patients who were admitted to the emergency department with the diagnosis of anterior shoulder dislocation participated in this study. The diagnosis of shoulder dislocation was established in the emergency department with physical examination and anteroposterior shoulder radiography. The method was applied only once to the patients in the sitting position by the same physician without using any help, traction, anesthesia, analgesia, and myorelaxant. Results. The mean age of the patients was 37.3 ± 13.1 years. Among them, 36.8% n=7 were female and 63.2% n=12 were male. Recurrent dislocations were observed in 21.1% n=4 of the patients. The success rate of the method was 94.7% n=18. No complication was noted in the patients. The mean procedure time was 243 ± 38 seconds. Conclusion. Prakash’s method is a safe method for anterior shoulder dislocations that can be quickly performed with no need for sedation, assistance, and traction and has a high success rate.